Longitud de trabajo en endodoncia - Rodríguez, María Isabel (Revista Estomatología, 1992)
In endodontics is of great importance to choose an appropiate work system, for which literature has reported various methods in which the the electronic equipments seem to be trustfull, although they have severallimitations. In our system, the trational method is based on X-Ray and the clinic dentist’s judgment continue being the best chose.